A Catastrophic Failure to Build a Massive Galaxy around a Supermassive Black Hole at z=3.84 - Schramm M; Rujopakarn W; Silverman JD; Nagao T; Schulze A; Akiyama M; Ikeda H; Ohta K; Kotilainen J (IOP PUBLISHING LTD, 2022)
We present observations of the stellar and molecular gas mass of SDSS J163909+282447.1, a luminous quasar at z = 3.84 with an extreme mass for a supermassive black hole (SMBH; M-BH 2.5 x 10(10) M-circle dot). The local SMBH mass-galaxy mass relation predicts a massive host galaxy with M-stellar greater than or similar to 10(12) M-circle dot for this quasar. Based on sensitive near-infrared imaging with adaptive optics (AO) using Subaru, the stellar light from the host is undetected, thus resulting in an upper limit on the mass, M-stellar < 6.3 x 10(10) M-circle dot, a factor of greater than or similar to 16 less than expected. The CO(4 - 3) observations at 0 ''.2 resolution using the Atacama Large Millimeter/submillimeter Array indicate a molecular gas mass from CO of M-H2 similar to 4.5 x 10(9) M-circle dot and a dynamical mass within a radius of 0.45 +/- 0.2 kpc of M-dyn = 4(-4)(+10) x 10(10) M-circle dot. With the SMBH accounting for similar to 60% of the dynamical mass and considering the amount of molecular gas, we find an upper limit on the stellar mass to be M-stellar less than or similar to 1.5 x 10 10 M-circle dot, a value consistent with the limit from Subaru AO imaging. Based on these results, this SMBH has one of the largest host stellar mass deficits known given its SMBH mass; hence, it is unclear how to grow a SMBH/host galaxy to such a state since there is not enough molecular gas available to form a substantial amount of stellar mass to make up for the difference. Any physical model is likely to require an earlier phase of super-Eddington accretion onto the SMBH.